Inflammation and the Migration of Mesenchymal Stem Cell - Reza Maulana; Nur Wahyuniati; Imai Indra (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Mesenchymal stem cells are adult non-hematopoietic stem cells with multilineage proliferation and differentiation capabilities. This type of stem cell has the multipotent ability to differentiate into osteocytes, tenocytes, adipocytes, chondrocytes and  bone marrow stromal cells. The migration mechanism of mesenchymal stem cell is not yet fully understood, but based on studies  that  have  been  done  recently  by  the  researchers  worldwide  shown  that  the inflammatory process plays an important role for mesenchymal stem cell migration. A number of chemokine that plays a role in the migration of mesenchymal stem cells such as MCP-1 (CCL2), CXCL8, RANTES (CCL5), LL-37, integrin β1, CD44 receptor, CCR2, CCR3, and tyrosine kinase receptors for the following growth factors: IGF -1, PDGF-bb, HGF and VEGF